The Abyssinian connection? - Zacharie Mochtari de Pierrepont (Revue des Mondes Musulmans et de la Méditerranée)
Under the Rasūlid sultans of Yemen (r. 626-858/1229-1454), Abyssinia was famed for its gold, slaves and eunuchs, with a taste for imported cotton clothes and precious fabrics. It became an important partner of Yemen with the rise of the Wālāsmāʿ Sunni dynasty (r. 684-966/1285-1559) in Ifāt and their control of the port of Zaylaʿ, the main Abyssinian maritime outlet to the Red Sea. But relationships between Abyssinia and Yemen were not only anchored in trade and political considerations: Islamic scholars also interacted together extensively. This article proposes a first assessment and analysis of the scholarly relations between Yemen and Abyssinia in the 7th-9th/13th-15th centuries. Despite the scarcity of historiographical narrative sources, it illustrates that, on the one hand, Yemeni scholars participated time and again in the spread of Islam in Abyssinia between the 6th/12th and the 9th/15th century. On the other hand, the importance of scholars from Abyssinian origin in Yemen itself seems to have been greatly overlooked, even though many prominent Yemeni ʿulamāʾ and mystical figures of the 8th/14th and 9th/15th centuries had Abyssinian roots and played a considerable role in shaping the local Yemeni and regional scholarly environment. In this dual process of interactions and migrations emerge a glimpse of the Red Sea scholarly circulations and their dynamism, an Abyssinian connection with distinct channels of knowledge transmission and specific networks maintained between the two shores of the Red Sea.